Peningkatan Kemampuan Anak Dalam Membaca Al-Quran Sesuai Dengan Makhraj Huruf Metode Card Sort Di Kelas V Uptd SD N 08 Muaro Sungai Lolo - Zaima, Zaima (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
Teaching methods are strategies educators use to ensure the teaching and learning process runs effectively. The problem addressed in this study is students’ difficulty in reading the Qur’an accurately, particularly in pronouncing letters according to their makhraj and distinguishing between long and short recitations, resulting in a lack of fluency. This issue arises due to the lack of variety in teaching methods. To address this problem, the researcher applied, trained, and guided students through additional instruction using the "Card Sort" method. This approach aimed to improve students’ ability to read the Qur’an correctly, including proper makhraj pronunciation and accurate long and short recitations, specifically for fifth-grade students at SDN 08 Muaro Sungai Lolo. This research employed a Classroom Action Research (CAR) design. The subjects were 20 fifth-grade students at SDN 08 Muaro Sungai Lolo, consisting of 11 male and 9 female students. The CAR was conducted in two cycles, with each cycle consisting of one meeting. The research process included four stages: planning, implementation, observation, and reflection. Data collection was carried out through observation and written tests.